Development of electronic rain gauge system - Muhammad Mahbubur, Rashid; M. Rabani bin , M.Romlay; M.M, Ferdaus; Abdullah , Al-Mamun (Engineering and Technology Publishing, 2015)
Rainfall measurement system is a useful tool in weather measurement system. In tropical country such as Malaysia, rainfall measurement for agricultural and weather forecasting system is very important. Sampling-related tipping-bucket (TB) rain gauge measurements have significant errors for short time estimation. In this paper, a stable electronic rain gauge system with comprehensive data manipulation is designed and developed. This project used two major systems (a) tipping bucket with potentiometer and (b) capacitive sensor. Data is recorded and analyzed before the output is displayed. The system measures rainfalls accurately, saves the data reading and shows specific calculated for display.